Alkalinity, Major and Trace Elements as Hydrological Tracers in Different Seasons: Implications for the Origin of Hot Springs in Non-Volcanic Areas, Odisha, India - Snehal V Dewalkar; Nishant Shinde; Manmeet Kaur; Prabhjot Singh Bhuie; Arti Hadap; Shivmurti B Kshetri (International Journal of Hydrological and Environmental for Sustainability, 2024)
During the rainy season, surface water can infiltrate and mix with groundwater, making it difficult to identify different groundwater sources. In addition, mixing of water from different sources over time can obscure the original characteristics of groundwater. In this study, we used geochemical analyses such as alkalinity, major elements, hydrological modelling and long-term monitoring before, during and after the rainy season to understand the changes in concentrations, and determine the origin of groundwater sources despite different seasonal conditions. The data from this study was taken from a previous study and examined 18 water samples with different locations and weather conditions. Determination of 9 elements including alkalinity and trace elements was conducted as the main elements in this study. In the experiment, water temperature, pH, alkalinity, and free CO content were measured in situ from non-volcanic hot water, Odisha, India. In the process, the water was put into two polypropylene bottles, and cation and anion analyses were conducted in the laboratory. The results showed that seasonal differences clearly affected the changes in alkalinity concentration of each hot spring. However, hot springs with higher alkalinity experienced larger changes. In contrast, the analysed chlorine (Cl) concentrations < 100 mg/L were more susceptible to shifts due to monsoon, whereas Cl concentrations > 100 mg/L were more homogeneous despite the influence of monsoon (seasonal differences). Differences in the rainy season affected the concentration changes in Attri, Tarabalo and Deulajhari hot springs. Meanwhile, hot springs dominated by meteoric water such as Badaberena, Taptapani and Boden are less affected. This proves that Attri, Tarabalo and Deulajhari hot springs originate and are dominated by deep groundwater.